Effectiveness of audio-visual and poster media in improving handwashing knowledge among adolescents - Latif, Farida; Wahyuni, Sri; Latif, Sarifudin Andi (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2025)
Introduction: Handwashing with soap (HWWS) is a key indicator of clean and healthy living behavior and plays a crucial role in preventing infectious diseases among adolescents. Schools are strategic settings for health promotion, and educational media such as audiovisual materials and posters are widely used to improve students’ knowledge and hygiene practices. This study aimed to determine the effectiveness of health education using audiovisual media and posters in increasing adolescents’ knowledge of HWWS. Methods: This quasi-experimental study employed a one-group pretest–posttest design involving 37 eighth-grade students at SMPN 5 Kendari. Participants received health education delivered through audiovisual media and posters. Knowledge was assessed using pretest and posttest questionnaires. Data were analyzed using univariate and bivariate methods, including the Wilcoxon Signed Rank Test due to non-normal data distribution. Results: The findings showed an increase in the mean knowledge score from 56.89 to 63.78 after exposure to audiovisual media, and from 57.43 to 74.46 after exposure to poster media. The Wilcoxon test indicated significant differences between pretest and posttest scores for both press (p = 0.000), confirming the effectiveness of both approaches. Poster media demonstrated a greater improvement in students’ HWWS knowledge compared to audiovisual media. Conclusion: Health education using both audiovisual and poster media effectively increased adolescents’ HWWS knowledge, with poster media showing superior impact. These results highlight the importance of utilizing a variety of educational tools in school-based hygiene promotion. Schools are encouraged to integrate both media regularly in health education activities and collaborate with local health centers to promote continuous HWWS. Future studies should explore more advanced audiovisual content and evaluate long-term behavioral changes among students.